PENGARUH KOMITMEN KERJA DAN KONFLIK KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA CV SUMBER AYEM MANGUNREJO KEDIRI - Arianik, Ragil; Sutapa, Heru; Jatmiko, Udik (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARI, 2023)
This study aims to determine the effect of work commitment and work conflict on turnover intention at CV Sumber Anyem Mangunrejo Kediri. This study uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. While the analysis used is the validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and the coefficient of determination. Sampling in this study used a saturated sample with consideration of all employees of CV Sumber Anyem Mangunrejo Kediri, amounting to 30 people based on the results of research conducted. The results of this study use the SPSS 22.0 program using a significant level of 5% or 0.05 with the results (1) partially work commitment has a significant effect on turnover intention with a significant value of 0.000 > 0.05 which means H1 is accepted and Ho1 is rejected. (2) partially work conflict has no significant effect on turnover intention with a significant value of 0.325 <0.05, which means H2 is rejected and Ho2 is accepted. (3) simultaneously work commitment and work conflict have a significant effect on turnover intention with a significant value of 0.000 <0.05, which means Ha3 is accepted and Ho3 is rejected